2019
DOI: 10.1681/asn.2018060609
|View full text |Cite
|
Sign up to set email alerts
|

Indoxyl Sulfate and p-Cresyl Sulfate Promote Vascular Calcification and Associate with Glucose Intolerance

Abstract: BackgroundProtein-bound uremic toxins indoxyl sulfate (IS) and p-cresyl sulfate (PCS) have been associated with cardiovascular morbidity and mortality in patients with CKD. However, direct evidence for a role of these toxins in CKD-related vascular calcification has not been reported.MethodsTo study early and late vascular alterations by toxin exposure, we exposed CKD rats to vehicle, IS (150 mg/kg per day), or PCS (150 mg/kg per day) for either 4 days (short-term exposure) or 7 weeks (long-term exposure). We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 56 publications
6
109
0
Order By: Relevance
“…Both proteins stimulate the phenotypic switch of VSMCs into bone-like cells through activation of the p38 MAPK pathway and oxidative stress pathways [31,32]. As mentioned above, our study also revealed that, after proteomic analysis of aortic tissue from either IS or PCS exposed CKD rats, coagulation pathways (intrinsic/extrinsic prothrombin activation pathways) play a central role in the arterial calcification process [21]. A close link between coagulation and inflammation exists as coagulation factors, such as fibrinogens and prothrombin, also belong to the acute phase proteins [22].…”
Section: Inflammation and Coagulation Signaling Pathwayssupporting
confidence: 75%
See 2 more Smart Citations
“…Both proteins stimulate the phenotypic switch of VSMCs into bone-like cells through activation of the p38 MAPK pathway and oxidative stress pathways [31,32]. As mentioned above, our study also revealed that, after proteomic analysis of aortic tissue from either IS or PCS exposed CKD rats, coagulation pathways (intrinsic/extrinsic prothrombin activation pathways) play a central role in the arterial calcification process [21]. A close link between coagulation and inflammation exists as coagulation factors, such as fibrinogens and prothrombin, also belong to the acute phase proteins [22].…”
Section: Inflammation and Coagulation Signaling Pathwayssupporting
confidence: 75%
“…Our laboratory recently reported that both IS and PCS are important harmful vascular toxins, as they trigger moderate to severe arterial media calcification in CKD rats, which goes along with the activation of inflammation (i.e., acute phase response signaling pathway) and coagulation (i.e., intrinsic/extrinsic prothrombin activation pathway) pathways linked with increased circulating glucose levels and insulin resistance. These changes were even observed after four days of IS or PCS exposure, i.e., before arterial media calcifications had developed, indicating that the IS/PCS mediated upregulation of inflammation and coagulation precedes the vascular calcification process [21]. Additionally, in this study, escape from uremic-toxin-induced calcification was linked with liver X receptor and farnesoid X/liver X receptor signaling pathways, discussed more in detail below.…”
Section: Molecular Mechanisms By Which Is and Pcs Induce Vascular Calmentioning
confidence: 52%
See 1 more Smart Citation
“…Similarly, IS administered orally promotes aortic calcification in hypertensive rats with normal kidney function [59,60]. More recently, Opdebeeck et al [61] showed that exposure to IS in a rat model with CKD induced by adenine diet increases aortic calcification. The amount of aortic calcification is associated with IS plasma concentration.…”
Section: Evidence Of a Role In Vascular Calcificationmentioning
confidence: 99%
“…In addition to playing a role in the progression of endothelial dysfunction, PCs were found to be correlated with image-proven vascular calcification and cfPWV, together with an inverse relationship with the estimated glomerular filtration rate of CKD patients [13]. Recently, Opdebeeck et al proved that short-and long-term exposures to PCs promoted aortic inflammation and calcification, respectively, in vivo through the acute-phase response and coagulation signaling pathway [24]. In a cross-sectional study, Rossi et al reported that serum PC was independently associated with interleukin 6 and PWV, highlighting its role in inflammation and its contribution to CV damages in CKD stages 3-4 [25].…”
Section: Discussionmentioning
confidence: 99%